The Contribution of Extracellular Vesicles From Senescent Endothelial and Vascular Smooth Muscle Cells to Vascular Calcification - Mas-Bargues, Cristina; Borrás, Consuelo; Alique, Matilde (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification is an irreversible pathological process associated with a loss of vascular wall function. This process occurs as a result of aging and age-related diseases, such as cardiovascular and chronic kidney diseases, and leads to comorbidities. During these age-related diseases, the endothelium accumulates senescent cells, which stimulate calcification in vascular smooth muscle cells. Currently, vascular calcification is a silent pathology, and there are no early diagnostic tools. Therefore, by the time vascular calcification is diagnosed, it is usually untreatable. Some mediators, such as oxidative stress, inflammation, and extracellular vesicles, are inducers and promoters of vascular calcification. They play a crucial role during vascular generation and the progression of vascular calcification. Extracellular vesicles, mainly derived from injured endothelial cells that have acquired a senescent phenotype, contribute to calcification in a manner mostly dependent on two factors: 1) the number of extracellular vesicles released, and 2) their cargo. In this review, we present state-of-the-art knowledge on the composition and functions of extracellular vesicles involved in the generation and progression of vascular calcification.